President’s Speech Act In Vlog - Risa Mufliharsi (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
This paper is a research report on the analysis of utterances of Mr. Joko Widodo as President of Indonesia and vloggers in vloggers’ vlogs. This study analyzes the rules of Mr. Joko Widodo as President conducting his utterances at vlog as social media. He realized that nowadays people of Indonesia always tuning in digitalization. In this media, people can see directly his activities as a president. Both the vlogs showed the interactions with Mr. Joko Widodo in different purposes and styles. The vlogs taken from Skinnyindonesia24 which has 66.000 subscribers and Arif Muhammad which has 92.000 subscribers. The data taken and analyzed both qualitative and quantitative data . The result of this research imply both of the vlogs Mr. Joko Widodo applies politeness strategies even in informal situation both vlogs. He acts extraordinary pragmatic forces and high politeness. So that, the audience gets the emotion, sympathy and persuasion of those who watches of them at vlog.Keywords: president, politeness, speech acts, vlog